EXPRESSIONS OF PERCEIVED SUSCEPTIBILITY TOWARD NASOPHARYNGEAL CARCINOMA - Jia Yiing Lucy Ho; Su Hie Ting; Yuwana Podin (Universitas Airlangga, 2022)
Introduction: Perceived susceptibility to diseases influences intentions to undertake health protective measures. Methods: The study investigated perceived susceptibility of nasopharyngeal carcinoma (NPC) among Malaysians, focusing on their expressions of disease susceptibility before and after reading an NPC health pamphlet. Method: A total of 65 participants in Kuching and Kota Samarahan, Malaysia, aged 13 to 65, were interviewed on their perceptions of their risk of getting NPC. Results: The thematic analysis of the interviews revealed several levels of perceived susceptibility to NPC, namely, 1) not susceptible to NPC, 2) may be susceptible to NPC, 3) susceptible to NPC, and 4) not knowing much about susceptibility to NPC. The expressions the participants used revolved around “living a healthy life”, “second-hand smoker”, “polluted air” and “eat preserved or salted food”, indicating perceived risk factors of NPC. Conclusion: Some mentioned family history and ethnic background as risk factors. After reading the NPC pamphlet, the participants gave the same reasons but with more specific details on the symptoms and types of food associated with NPC. The study indicated that the NPC pamphlet can increase awareness of NPC because additional reasons given for NPC susceptibility after reading the pamphlet were signs of cancer, age, and NPC incidence in Malaysia.